If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1x = 4x + -10 Reorder the terms: 5 + -1x = -10 + 4x Solving 5 + -1x = -10 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5 + -1x + -4x = -10 + 4x + -4x Combine like terms: -1x + -4x = -5x 5 + -5x = -10 + 4x + -4x Combine like terms: 4x + -4x = 0 5 + -5x = -10 + 0 5 + -5x = -10 Add '-5' to each side of the equation. 5 + -5 + -5x = -10 + -5 Combine like terms: 5 + -5 = 0 0 + -5x = -10 + -5 -5x = -10 + -5 Combine like terms: -10 + -5 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| 150x+50y=1800 | | 7y=147 | | 9x^2-35x+25=0 | | 9y-2.1=5y+3.5 | | 5x=74 | | 2x(x)= | | z/-9=-2.5 | | 8n^2-24n-244=0 | | 0=x^2-2x+24 | | 05x+65=180 | | 6x+x-5=2(x-10) | | x^3/2-15x^1/2=0 | | 5x+7=-x-17 | | x+y-9=39 | | 8w=-52 | | 42x^2y^3/9x^6y^-6 | | 7n-7n=6(-2n-10)+4(8n-2) | | x+8.6=36.2 | | (x-2)(-y)= | | 0=x^2+8x-9 | | 4x+36=18x-48 | | 2x^2=x^2+28x | | -7x+2+5x=24 | | f(x)=4x(cos(5x)) | | 8n+5=4n-11 | | p=5x-4y+3z | | 2Y+X+21=0 | | y/5=-5.5 | | 12x-6=3(3x+4) | | a(n)=7+(n-1)3 | | -10h-6=-2over-5 | | -36+8x=2(2+8x) |